European opera classics in the mirror of Spanish zarsuela - Nazymchuk, Dariia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study: Italian opera, which dominated at the musical theater of Europe in the 18th and 19th centuries, influenced the development of a number of national genres, such as the German singspiel (Singspiel) and romantic opera (romantische Oper), French comic and grand opera (opera comique and grand opéra), English ballad opera. In studies that consider the dynamics of the development of the opera genre in Germany, Austria, France and other countries, such influences are analyzed. The influence of Italian opera is also present in the Spanish zarzuela, a genre that is much less covered in musicological works. Analysis of three zarzuelas — «El barbero de Sevilla» by Geronimo Gimenez and Manuel Nieto, «El dúo de La Africana» by Manuel Fernández Caballero and «La Golfemia» by Luis Arnedo — shows that in the zarzuelas the elements of composition and drama were borrowed from Italian operas. The Spanish zarzuela has not yet been an object of scientific studies in Ukrainian musicology: neither the dynamics of the genre's development nor individual samples have been considered. This determines the relevance of this study and its scientific novelty. The main objective of the study: based on the analysis of the Spanish zarzuelas, to reveal the connections of the genre with the European opera tradition (in particular, Italian and French); to establish the peculiarities of the functioning of the genre canon of opera in the conditions of the national Spanish culture. The research uses general scientific and special musicological methods. The first ones include: 1) the method of generalization (on the basis of studying a number of musicological publications, information on the zarzuela genre is summarized); 2) comparative method (fragments of classical operas quoted in Spanish zarzuelas are compared with the originals). Among the special musicological methods, the method of analyzing the means of musical expressiveness is used. Results and conclusions. In the process of genre development, two varieties of zarzuela were formed — small and large (zarzuela chico and zarzuela grande). The small zarzuela has the following characteristics: 1) consists of one act, contains up to ten musical numbers; 2) has a small number of characters; 3) uses plots of everyday life, mostly comedic ones; 4) relies on popular musical intonations; 5) contains more spoken text than vocal numbers. The works analyzed in the article are small zarzuelas. There are borrowings from Italian and French operas in their plots and musical text. The musical text of famous opera works is present in zarzuelas in the form of allusions and quotations. The verbal text of zarzuel contains references to certain operas or mentions of them. Musical elements of European opera classics are reproduced in zarzuelas on two levels: compositional and performing. The use of plot and musical borrowings from classical operas in zarzuelas is associated with the strengthening of the comedic, parodic nature.